(2,8+3,2+3,9):3=3,3 Ето и будет ответ на ето задание
<span>1)(3х+1):(-1/4)=-4
3х+1=-4*(-1/4)
3х+1=1
3х=1-1
3х=0
х=0:3
х=0
2) p:(-7/26)=2 11/14
р=2 11/14*(-7/26)
р=-39/14*(-7/26)
х=3/4
</span>
1 - 2sin x*cos 3x = 2cos 3x - sin x
1 + sin x = 2cos 3x + 2sin x*cos 3x = 2cos 3x*(1 + sin x)
(1 + sin x)(1 - 2cos 3x) = 0
1) 1 + sin x = 0
sin x = -1; x1 = -pi/2 + 2pi*k
2) 2cos 3x = 1
cos 3x = 1/2
3x2 = pi/3 + 2pi*n; x2 = pi/9 + 2pi/3*n
3x3 = -pi/3 + 2pi*m; x3 = -pi/9 + 2pi/3*m
9 0.28 0.16 1/3 9 0,28 0.16 1/3 11,25 0.35 5/12